Kekuatan Agama dan Kearifan Lokal dalam Proses Kebangkitan Masyarakat Yogyakarta Pascagempa - Ali Imron; Aat Hidayat (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
This qualitative research intends to explore the religious strength and local  wisdom in the process of society revival in Kasongan Bantul Yogyakarta after the earthquake on May 27, 2006. The main questions which will be answered are: (1) How are the form and construction of religious strength and local wisdom in the Kasongan area, so they can play the important roles in the process of Kasongan society resurrection after the earthquake?; (2) How is the strategy of Kasongan society in using the religious strength and local wisdom in the process of their revival after the earthquake? The substance that becomes the object of this research consists of religious texts, leaders of society, social institutions, and local cultural systems. The used theoretical frameworks are religious strength theory and hermeneuticsphenomenology theory. The methods of collecting data are documenting the important data, observation, and interview. Then, which analyzed by a functional analysis theory. Theoretically, this research hopefully is able to be useful in contributing to the formulation of culture-based disaster theological discourse in Indonesia. In addition to, the results of this research are expected to be a contribution for Indonesia especially, and for the international world generally, in natural disaster reduction efforts, both in the perspective of social science and religious perspective. After conducting in-depth research in the Kasongan area, the researcher conclude that: (1) Kasongan society have big capitals to revive from adversity immediately after the earthquake, of which are the theological capital and cultural capital, (2) with these capitals, of which includes guyub strategy, getok tular, and build cooperation with various agencies, Kasongan society revive immediately and rearrange Kasongan pottery business that has been destroyed by an earthquake.